Cutaneous sarcoidosis due to immune‐checkpoint inhibition and exacerbated by a novel BRAF dimerization inhibitor - J. P. Pham; P. Star; S. Wong; D. L. Damian; R. P. M. Saw; M. J. Whitfeld; A. M. Menzies; A. M. Joshua; A. Smith (Wiley, 2021)
Abstract Sarcoidosis is a non‐infective granulomatous disorder of unknown aetiology, with cutaneous involvement affecting up to 30% of patients. Drug‐induced sarcoidosis has been reported secondary to modern melanoma therapies including immune‐checkpoint inhibitors and first generation BRAF inhibitors such as vemurafenib and dabrafenib. Herein, we report a case of cutaneous micropapular sarcoidosis that first developed on immune‐checkpoint inhibition with ipilimumab and nivolumab for metastatic melanoma, which was exacerbated and further complicated by pityriasis rubra pilaris‐like palmar plaques upon transition to a next‐generation BRAF‐dimerisation inhibitor. Both the micropapular eruption and palmar plaques rapidly resolved after cessation of the novel BRAF‐inhibitor and concurrent commencement of hydroxychloroquine. It is unclear how inhibition of BRAF‐dimerisation results in granuloma formation, though upregulation of TH1/TH17 T‐cells and impairment of T‐reg cells may be responsible. Clinicians should be aware of the potential for exacerbation of sarcoidosis when transitioning from immune‐checkpoint inhibitors to these novel BRAF‐dimerisation inhibitors, particularly as their uptake in treating cancers increases beyond clinical trials. Further studies are required to assess whether these next‐generation agents can trigger sarcoidosis de‐novo, or simply exacerbate pre‐existing sarcoidosis.